FACTORS INFLUENCING THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) AMONG HEALTH WORKERS IN KIRYANDONGO GENERAL HOSPITAL: ACROSS SECTIONAL STUDY. - Akello, Jacky Oguta; Awoi, Ronald; Omara, Tonny Mike (SJ Insights, 2024)
BACKGROUND PPE is equipment worn to minimize exposure to hazards that cause serious workplace injury and illness, which may result from contact with workplace hazards. Therefore, the study aimed to determine the factors influencing the use of personal protective equipment among health workers in Kiryandongo General Hospital. Methodology The study was descriptive and cross-sectional in design, using quantitative methods for data collection and analysis done using SPSS version 29. A simple random sampling method was used to obtain the 41 respondents. Data was collected using a questionnaire. Most of the health workers, 97.6% have a positive attitude towards PPE use, the Majority 63.4% always use PPEs, and the majority of the respondents 90.2% reported that accidental exposures influence the use of PPEs. The majority 51.2 % indicated that PPE design influences its use. Conclusion Utilization of PPEs among health workers in Kiryandongo Hospital is generally high among the diploma holders, PPE design and accidental exposures were among the key factors influencing the use of PPEs. Recommendation Hospitals should provide ongoing PPE training, adhere to SOPs, and promote professional development. MOH should ensure proper PPE procurement. This implies that nurses must advocate for consistent PPE access, report exposures promptly, collaborate on selecting comfortable yet safe PPE, and ensure SOP adherence among all health workers.